A Randomized Controlled Trial of the Prescribed Stepper Walking Program in Preventing Frailty Among the Dwelling Elderly: Application of Comprehensive Geriatric Assessment. Issue 3 (July 2018) - Kuo, Mei-Chen; Chen, Ching-Min; Jeng, Chii
Abstract : This is the first article that described the effect of a prescribed stepper walking program based on comprehensive geriatric assessment in preventing the general fitness of older adults. An experimental design was conducted with 36 elderly individuals (experiment = 15, control = 21) who were asked to have a 30-minute stepper walking exercise twice per week in the research center. The effectiveness of the program would be evaluated in 8 weeks. The results indicated that the 6-minute walk test, body mass index, waist-hip ratio, body composition percentage, and 3-m up and go test improved after an 8-week exercise training in the experimental group.